Liquidity, Sentiment and Segmentation: A Survey of Closed-End Fund Literature - Mary Fletcher (Journal of Accounting and Management Information Systems (JAMIS), 2013)
Closed-end funds have been a topic of lively debate for several decades. In this paper I focus on studies relating to liquidity, sentiment and segmentation and, in particular, on studies that investigate closed-end country funds. I extend the previous survey by Dimson & Minio-Kozerski (1999) by adding in more recent contributions to the closed-end fund debate; and by including more of a discussion of sentiment, segmentation and country funds I complement the recent survey by Cherkes (2012). In addition I provide summaries of over 40 key papers in these areas, listing the sample and sample period, the theory examined and the findings of each paper.
Keywords: G12; G15; G23; F3; 650; Closed-end Fund; Closed-end Country Fund; Investment Trust; International Finance; International Financial Markets; Liberalization